Carbon Dioxide Flushing Technique to Prevent Cerebral Arterial Air Embolism and Stroke During TEVAR. (April 2016) - Kölbel, Tilo; Rohlffs, Fiona; Wipper, Sabine; Carpenter, Sebastian W.; Debus, Eike Sebastian; Tsilimparis, Nikolaos
Purpose: To describe the technique of carbon dioxide (CO2 ) flushing of thoracic stent-grafts to reduce the risk of cerebral air embolism.Technique: To remove room air, thoracic stent-grafts were preoperatively flushed 2 minutes with carbon dioxide from a cylinder connected to the flushing chamber of the captor valves of Zenith custom-made endografts; this was followed by the standard saline flush. Thirty-six patients undergoing thoracic endovascular aortic repairs (TEVAR) involving the ascending aorta and the aortic arch received CO2 -flushed Zenith endografts. One patient with a highly calcified arch experienced a minor stroke.Conclusion: Arterial air embolism is a potentially underappreciated problem of aortic endografting, especially in the proximal segments of the aorta. CO2 flushing may have the potential to reduce air embolization during TEVAR.